ANALISIS PENGARUH SOCIAL MEDIA MARKETING, ELECTRONIC WORD OF MOUTH, DAN E-SERVICE QUALITY TERHADAP MINAT BELI PADA E-COMMERCE TOKOPEDIA (STUDI KASUS PADA MAHASISWA FEB UPNVJ) - Candra Dewa Wijaya Kusuma (2022)
This research is a quantitative study that aims to determine whether there is an influence between social media marketing, electronic word of mouth and e-service quality on purchase intention in e-commerce Tokopedia (a case study on FEB UPNVJ students). This study used 100 respondents, with purposive sampling technique. The analysis technique used is the path analysis method and data processing is done through SmartPLS 4.0. The results of the test obtained (1) social media marketing has a positive and significant effect on purchase intention in e-commerce Tokopedia at FEB UPNVJ. (2) electronic word of mouth has a positive and significant effect on purchase intention in e-commerce Tokopedia at FEB UPNVJ. (3) E-service quality has no effect on purchase intention in e-commerce at FEB UPNVJ.